Fight Like a Tiger Win Like a Champion - Darmadi Darmawangsa (ELEX Media, 2006)
Berapa banyak buku motivasi dan pengembangan diri yang sudah Anda baca selama ini? Adakah pengaruhnya yang signifikan dalam peningkatan kualitas hidup Anda? Atau justru Anda makin tidak percaya akan adanya kesuksesan? Apa rahasia di balik fenomena sukses-gagal dan motivasi diri? Buku ini berisi langkah-langkah utama dalam mewujudkan hidup yang berkualitas menuju performa puncak, yang disusun dengan gaya bahasa yang enak dibaca, mudah dipahami, dan terstruktur rapi. Tidak ada jalan pintas menuju sukses. Jika hanya ada satu buku yang layak Anda baca tahun ini untuk meningkatkan kualitas hidup Anda, maka inilah bukunya! "To master your life you have to start from the foundation of the truth. This Book will reveal the foundation which you can apply to gain unlimited success. I recommend to everyone to read and apply it." JACK CANFIELD, co-creator of #1 New York Times best selling Chicken Soup for the Soul series, author of The Success Principles. "This is a wonderful, uplifting, and inspiring book full of practical wisdom and guidance which you can use to achieve your Core Desire and to become a champion. Read it now!" JACK M. ZUFFELT, author of #1 best selling book The DNA of Success. "Darmadi Darmawangsa and Imam Munadi has written one of the best books ever on personal success and achievement. It is full of powerful, practical ideas you can use to improve every part of your life!" BRIAN TRACY, author of Goals! "Fight Like a Tiger Win Like a Champion is a powerful book which combines the wisdom of many of the greatest thinkers and the philosophy of success in the simplest way. Darmadi and Imam are champions with a tiger`s heart." JAMES GWEE, MBA, Director of Academia Eduction & Training.